The Connection Between Selected Caspases Levels in Bronchoalveolar Lavage Fluid and Severity After Brain Injury - Siwicka-Gieroba, Dorota; Terpilowska, Sylwia; Robba, Chiara; Barud, Małgorzata; Kubik-Komar, Agnieszka; Dabrowski, Wojciech (Frontiers in Neurology, 2022)
Objective The interaction between the brain and lungs has been the subject of many clinical reports, while the exact impact of brain injury on the physiology of the respiratory system is still subject to numerous experimental studies. The purpose of this study was to investigate the activation of selected caspases levels in bronchoalveolar lavage fluid (mini BALF) of patients after isolated brain injury and their correlation with the severity of the injury. Methods The analysis was performed on patients who were admitted to the intensive care unit (ICU) for severe isolated brain injury from March 2018 to April 2020. All patients were intubated and mechanically ventilated. Mini BALF was collected within the first 6–8 h after trauma and on days 3 and 7 after admission. The concentrations of selected caspases were determined and correlated with the severity of brain injury evaluated by the Rotterdam CT Score, Glasgow Coma Score, and 28-day mortality. Results Our results showed significantly elevated levels of selected caspases on days 3 and 7 after brain injury, and revealed apoptosis activation during the first 7 days after brain trauma. We found a significant different correlation between the elevation of selected caspases 3, 6, 8, and 9, and the Glasgow Coma Score, Rotterdam CT scale, and 28-day mortality. Conclusions The increased levels of selected caspases in the mini BALF in our patients indicate an intensified activation of apoptosis in the lungs, which is related to brain injury itself via various apoptotic pathways and correlates with the severity of brain injury.